Implementation of a Pediatric Posttonsillectomy Pain Protocol in a Large Group Practice - Luk, Lauren J; Mosen, David; MacArthur, Carol J; Grosz, Anna H (Otolaryngology-head and neck surgery, 2016)
In response to the increased risk of respiratory failure and death after tonsillectomy related to codeine use, Kaiser Permanente Northwest restricted use of opioids in patients <7 years old via electronic health record (EHR). However, opioids could be prescribed at physician discretion by overriding the EHR. This study aims to examine protocol compliance in a large group practice using EHR order sets and complication rates as compared with historical data. Case series with chart review. Ambulatory care within a health maintenance organization. Procedural codes were used to identify children <7 years old who underwent tonsillectomy or adenotonsillectomy approximately 1.5 years before and after implementation of EHR protocol (n = 437). Primary outcome was opioid pain prescriptions received by patients. Secondary outcomes were emergency or urgent care utilization, postoperative bleeding, nausea, vomiting, dehydration, death, and reasons for prescribing opioid pain medication after EHR protocol implementation. Chi-square analysis and Fischer's exact testing were used to compare differences in event rates. Implementation of an age-based narcotic protocol significantly decreased physician narcotic prescribing from 82.2% to 15.4% (P < .0001). The most common reason for narcotic prescription after the intervention was the report of inadequate pain control by phone call (35%). There was no significant difference in rate of emergency or urgent care utilization between pre- and postimplementation groups (4% vs 6%, P = .29). Implementation of an age-based narcotic restriction for posttonsillectomy patients using an EHR order set is an effective and safe way to influence physician prescription practices.